Construction of multi-wave complexiton solutions of the Kadomtsev-Petviashvili equation via two efficient analyzing techniques - Abdullahi Yusuf; Tukur Abdulkadir Sulaiman; E.M. Khalil; Mustafa Bayram; Hijaz Ahmad (Results in Physics, 2021)
This study aims to investigate the (2 + 1)-dimensional Kadomtsev-Petviashvili equation via the three-waves method through the Hirota bilinear form and the Kudryashov’s method. Multi-waves solutions and exponential function solutions are successfully extracted. To share more light to the physical features of the reported results, the interaction phenomenon of these obtained solutions are demonstrated by some 3-dimensional and contour plots. All the reported results have tested to satisfy the original nonlinear partial differential equation.